Disfunction of Wakalah Contract in Murabahah Financing of Sharia Banking in Indonesia - Muh. Shadiqul Fajri AF; Gagaring Pagalung; Muslimin H. Kara (Program Pascasarjana STIE Amkop Makassar, 2022)
Murabahah financing is the most dominant financing product in Islamic banking entities in Indonesia. Several factors make murabahah financing more dominant than other financing products, including; First, the murabahah financing scheme is simpler so that it is easier for the public to understand. Second, the amount of profit margin can be known at the beginning of the contract and is fixed until the financing period ends. The application of murabahah financing in Islamic banking in Indonesia uses the murabahah bil wakalah scheme. This study uses a descriptive-qualitative method with a normative theological approach using field research techniques that focus on the flow of the murabahah bil wakalah financing process. The results showed that there was an error in the application of the murabahah bil wakalah scheme where the murabahah and wakalah contracts were signed and agreed upon in the same assembly. This of course violates the rules in muamalah fiqh which makes a murabahah (buying and selling) contract turn into a qardh (debts) contract. So, the real transaction that occurs between the Islamic banking party and the customer is a debt-receivable contract transaction, not a sale and purchase agreement.